2012
DOI: 10.1016/s2225-4110(16)30073-6
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo Therapeutic Effect of Free Wanderer Powder (逍 遙 散 xiāo yáo sǎn, Xiaoyaosan) on Mice with 4T1 Cell Induced Breast Cancer Model

Abstract: In the present study, we investigated the therapeutic effect of a classical TCM formula, Free Wanderer Powder (逍遙散 xiāo yáo sǎn), in a breast cancer mouse model induced with estrogen-insensitive breast cancer 4T1 cells. Ovariectomized Balb/c mice (6-8 weeks) or sham mice were injected into the fourth mammary fat pad with 4T1 cells in which tumors were palpable 7 days after injection. On the eighth day, the mice were divided into 4 groups and tubefed daily with vehicle, Free Wanderer Powder (逍遙散 xiāo yáo sǎn) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“… 17 The formula comprises several herbs, including Atractylodis Macrocephale rhizoma , Bupleuri radix , Angelica sinensis , Poria , Glycyrrhizae radix , tree peony bark , Gardenia jasminoides , Paeonia lactiflora pall , mint , and roasted ginger , active components of which are identified to be genipside, paeonol, ferulic acid, paeoniflorin, and senkyunolide A (SenA). 18 – 20 TCM has been used for thousands of years for treating depression-related conditions in China, and Dan-zhi-xiao-yao-san has been proved to be one of the most effective formulae. Dong et al 21 demonstrated that the treatment of rats with general-ized anxiety disease using Dan-zhi-xiao-yao-san relieved the animals of depression symptoms by protecting neural cells in Papez’s circuit against apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“… 17 The formula comprises several herbs, including Atractylodis Macrocephale rhizoma , Bupleuri radix , Angelica sinensis , Poria , Glycyrrhizae radix , tree peony bark , Gardenia jasminoides , Paeonia lactiflora pall , mint , and roasted ginger , active components of which are identified to be genipside, paeonol, ferulic acid, paeoniflorin, and senkyunolide A (SenA). 18 – 20 TCM has been used for thousands of years for treating depression-related conditions in China, and Dan-zhi-xiao-yao-san has been proved to be one of the most effective formulae. Dong et al 21 demonstrated that the treatment of rats with general-ized anxiety disease using Dan-zhi-xiao-yao-san relieved the animals of depression symptoms by protecting neural cells in Papez’s circuit against apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao-yao-san and modified formula such as Dan-zhi-xiao-yao-san are most commonly used TCM formulas for treating multiple diseases such as depression in China and other Asia countries [17]. Based on TCM theory, Xiao-yan-san mainly used for promoting liver qi circulation, coursing the liver, nourishing liver blood and fortify the spleen [18][19][20]. Dan-zhi-xiao-yao-san is comprised of several herbs including atractylodismacrocephalerhizoma, bupleuri radix, angelicaesinensis, poria, glycyrrihizae radix, tree peony bark, gardenia jasminoides, paeonialactiflora pall, mint and roasted ginger [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Based on TCM theory, Xiao-yan-san mainly used for promoting liver qi circulation, coursing the liver, nourishing liver blood and fortify the spleen [18][19][20]. Dan-zhi-xiao-yao-san is comprised of several herbs including atractylodismacrocephalerhizoma, bupleuri radix, angelicaesinensis, poria, glycyrrihizae radix, tree peony bark, gardenia jasminoides, paeonialactiflora pall, mint and roasted ginger [18][19][20]. Although xiao-yao-san is one of the mostly commonly used formulas in China for treating depression, the active compound(s) and underlying mechanism are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao-yao-san and its modified formulations, including Dan-zhi-xiao-yao-san, are most commonly used in China and other Asian countries. According to the theories of TCM, Xiao-yao-san formulations repair the liver, promote liver qi circulation, nourish the blood in the liver and fortify the spleen, and these formulations are used clinically to treat a variety of conditions, including menopausal syndrome, anemia, functional uterine bleeding, hepatitis, chronic gastritis, pelvic inflammatory disease, anxiety and depression (8)(9)(10). Dan-zhi-xiao-yao-san is composed of Atractylodis macrocephale rhizoma, Bupleuri radix, Angelicae sinensis, poria, Glycyrrihizae radix, tree peony bark, Gardenia jasminoides, Paeonia lactiflora Pall, mint and roasted ginger.…”
Section: Introductionmentioning
confidence: 99%